Description of mechanical and biological factors affecting the bone-biomaterial(β tricalcium phosphate and chitosan), implanted in animal model (2013)
When designing a biomaterial, it is necessary to take into account both biological and mechanical factors that could affect its proper performance. From the biological point of view, when a biomaterial is implanted in bone tissues, it generates two interfaces: one between the foreign implanted material and the tissue surrounding it, and another one between inner parts of the material and the undegraded cells surrounding it. Cells neighboring bone surfaces, will try to invade the material to regenerate and reabsorb the defect created. This process is requires the production of type I and III collagen fibers, blood vessel growth, cell differentiation osteogenic and osteoclastogenesis which is the connection between the bone and the implanted material. However, these biological factors have a direct relationship with the mechanical factors involved in the healing process of injured tissues. The objective of this research is to obtain a synthetic, biocompatible and bioresorbable biomaterial. It is also easy to handle for the surgeon, and has a hardening time and moldability that facilitate its application. On the other hand, it has shown ability to stimulate bone formation at sites of non - union without adding other components